From Sustainability Commitment to Institutionalization: Assessing SDG Integration Across Jordanian Public Universities - Saja Wardat (Sustainability, 2026)
Universities play a pivotal role in advancing the United Nations Sustainable Development Goals (SDGs) through education, research, governance, operations, partnerships, and community engagement. However, limited evidence exists regarding the extent to which sustainability has been institutionally embedded within Jordanian higher education. This study presents an evidence-based comparative assessment of SDG institutionalization across ten Jordanian public universities using publicly available and verifiable institutional documents. Institutionalization was evaluated across eight dimensions: governance and strategy, education and curriculum, research and innovation, campus operations, partnerships, community engagement, inclusion and equity, and monitoring and reporting. A four-level institutionalization rubric ranging from “No eligible publicly verifiable institutional evidence” (0) to “Institutionalization with monitoring and reporting” (3) was applied to 80 university–dimension observations. The universities achieved a mean Institutional SDG Integration Index (ISDGI) of 66.3%, indicating that sustainability has progressed beyond isolated initiatives toward formal institutionalization across the sector. Monitoring and reporting demonstrated the highest level of institutionalization (80.0%), followed by campus operations (70.0%), while partnerships (60.0%) and community engagement (56.7%) remained comparatively less institutionalized. Overall, 71 of the 80 university–dimension observations (88.8%) reached at least the level of formal institutionalization. The findings indicate that sustainability has become embedded in many institutional structures within Jordanian public universities, although stronger institutionalization and systematic monitoring of external engagement, together with evidence-based evaluation, are needed to translate formal institutionalization into measurable societal impact. The proposed framework provides a transparent and replicable methodology for assessing SDG institutionalization in higher education institutions.